Adaptasi Karier Siswa SMK di Era Digital: Peran Kesadaran Diri dan Kemampuan Inovasi Teknologi - Wahyu S. G. Irianto; Erma Widayanti; Mukhammad R. Erwanenda (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
This study analyzes the influence of self awareness and technological innovation capability on career adaptability of vocational school students in the digital era. Using a descriptive correlational quantitative approach, this study involved 72 students from the Industrial Automation Engineering program at SMKN “Jaya”. Data were collected through a closed ended questionnaire based on a Likert scale and analyzed using multiple regression and partial correlation. The analysis results show that self awareness has a significant relationship with career adaptability (r = 0.881, p < 0.05), as does technological innovation capability (r = 0.861, p < 0.05). Simultaneously, these two variables contribute 81.7% to the career readiness of students, with self awareness playing a dominant role (47.8%) compared to technological innovation capability (33.9%). These findings affirm that self awareness is a key factor in enhancing the career readiness of vocational school students, while technological innovation capability strengthens their preparedness to face the technology based workforce. The implications of this research point to the need for integrating technology based learning strategies and strengthening self awareness in the vocational school curriculum to increase graduates' competitiveness in the dynamic digital era.